Potential correlation of allograft infiltrating group 2 innate lymphoid cells with acute rejection after liver transplantation - Sun, Jie; Zhou, Guang-Peng; Li, Shi-Peng; Chen, Xiao-Jie; Zhang, Jin-Ming; Jiang, Yi-Zhou; Cui, Bin; Zhang, Hai-Ming; Sun, Li-Ying; Zhu, Zhi-Jun (Frontiers in Immunology, 2022)
Accumulating evidence indicates the critical roles of group 2 innate lymphoid cells (ILC2s) in immunoregulation. However, the role of ILC2s in acute rejection after liver transplantation (LT) remains elusive. In this study, we analyzed the frequency, counts, and signature cytokines of ILC2s in liver transplant recipients by flow cytometric analysis and multiplex immunofluorescence assay. We also assessed the spatial distribution and correlation between hepatic ILC2s and Treg cells. The changes of ILC2s were dynamically monitored in the mouse LT model. We found that the frequencies of circulating ILC2s were comparable in liver transplant recipients with either rejection or non-rejection compared with the control group. The hepatic ILC2s counts were significantly increased in the rejection group than in the non-rejection and control groups, and a similar trend was observed for Treg cells. In the mouse LT model, allograft infiltrating ILC2s dramatically increased within 14 days post-transplant. The frequency of ILC2s in bone marrow significantly increased at 7 days post-transplant and rapidly decreased at 14 days after LT. Similarly, there was a significant increase in the frequency of splenic ILC2s within two weeks post-transplant. Multiplex immunofluorescence assay showed a close correlation between hepatic ILC2s and Treg cells by analyzing their spatial distribution and distance. In conclusion, the number of allograft inﬁltrating ILC2s was closely related to rejection after LT. Allograft inﬁltrating ILC2s may play inhibitory roles in posttransplant immune homeostasis, favoring resolution of liver allograft rejection by interacting with Treg cells or promoting the migration of Tregs cells into the liver allograft.